ChemInform Abstract: Assessment of the U3O7 Crystal Structure by X‐Ray and Electron Diffraction. Issue 50 (November 2016) - Leinders, Gregory; Delville, Remi; Pakarinen, Janne; Cardinaels, Thomas; Binnemans, Koen; Verwerft, Marc
Abstract: The crystal structure of U3 O7 obtained by oxidation of UO2 powder is investigated by powder XRD and SAED on single crystal grains.